2011
DOI: 10.1080/15374416.2011.581618
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relations Between Depressive Symptoms and Externalizing Behavior in Adolescence: Moderating Effects of Maltreatment Experience and Gender

Abstract: Among the explanations for the high rates of co-occurrence between depressive symptoms and externalizing behavior is the possibility of direct causal associations between the two symptom groups. However, the mechanisms by which co-occurrence arises may not be the same across etiologically significant variables. A gender-balanced sample of 303 adolescents (ages 9–12 at the first assessment) with carefully assessed histories of maltreatment experience and 151 demographically matched nonmaltreated adolescents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 62 publications
2
12
1
Order By: Relevance
“…Adolescent males who have experienced abuse in childhood are more likely to have poorer VIOLENCE AGAINST CHILDREN AND HUMAN CAPITAL IN SOUTH AFRICA numeracy and literacy skills as well as lower long term education levels. These results are consistent with the literature regarding gender differences on the sensitivity and ways of coping with stress caused by adverse childhood experience (Brensilver et al 2011;Gallo et al 2018;Maschi et al 2008). However, different from some past research, our results suggested a stronger relationship between childhood violence and short term females' physical health.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Adolescent males who have experienced abuse in childhood are more likely to have poorer VIOLENCE AGAINST CHILDREN AND HUMAN CAPITAL IN SOUTH AFRICA numeracy and literacy skills as well as lower long term education levels. These results are consistent with the literature regarding gender differences on the sensitivity and ways of coping with stress caused by adverse childhood experience (Brensilver et al 2011;Gallo et al 2018;Maschi et al 2008). However, different from some past research, our results suggested a stronger relationship between childhood violence and short term females' physical health.…”
Section: Discussionsupporting
confidence: 91%
“…Although adolescents may experience similar adverse effects to trauma from childhood violence, previous studies have suggested distinctions of coping responses between males and females (Gallo et al 2018;Maschi et al 2008). Specifically, adolescent males tend to react to stress by externalizing their behavior to express anger and act out aggressively, while females often internalize their behavior and therefore have higher levels of feelings of VIOLENCE AGAINST CHILDREN AND HUMAN CAPITAL IN SOUTH AFRICA 5 guilt, depression and anxiety (Brensilver et al 2011;Dunn et al 2012). As such, on the one hand, compared to their female counterparts, male adolescents are more likely to engage in risky behaviors, such as alcohol or substance abuse, and delinquency or criminality, which are detrimental to their physical health, academic achievement and education levels (Bask 2015;Holt et al 2008;Maschi et al 2008).…”
Section: Violence Against Children and Human Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 16 , 17 , 18 , 19 Childhood maltreatment (including harsh parenting) was measured using various methods. Six studies accessed official records, 15 , 20 , 21 , 22 , 23 , 24 and the remaining studies used self-reported experiences of maltreatment, where the participants reported experiences either as adolescents 13 , 19 , 25 , 26 , 27 , 28 , 29 , 30 or adults. 12 , 14 , 18 , 31 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…This sensitivity and the risk for depression may also result from a variety of feminine characteristics that emerge and intensify during adolescence such as hormonal changes, personality traits, attachment styles and maladaptive coping (Hankin & Abramson, 2001;Rose & Rudolph, 2006;Rudolph et al, 2006). Given these differences, gender has been studied as a moderator in the relationship between depression and other variables such as emotional intelligence (Salguero, Extremera, & Fernández-Berrocal, 2012), obesity (Rosa & Gonçalves, 2011), externalizing behavior (Brensilver, Negriff, Mennen, & Trickett, 2011) and cognitive emotional regulation strategies (Duarte, Matos, & Marques, in press).…”
Section: Introductionmentioning
confidence: 99%